The effect of both abrupt and strong enhancement of current in the semiconductor system : Schottky barrier containing a double barrier resonant-tunneling structure - Korol, Anatoliy; Tretyak, O.; Sheka, D. (My University, 2001)
The current-voltage characteristics for the double barrier resonant-tunneling structure incorporated into the depletion region of a Schottky barrier, are evaluated and analyzed. Hence both a very sharp and strong enhancement of current through the structure considered takes place for forward bias.
Keywords: current-voltage characteristic; resonant-tunneling structure; schottky barrier; вольт-амперна характеристика; тунельно-резонансна структура; бар’єр Шоткі; вольт-амперная характеристика; туннельно-резонансная структура; барьер Шоттки; кафедра фізики та професійної безпеки